2016
DOI: 10.16969/teb.03520
|View full text |Cite
|
Sign up to set email alerts
|

Mardin ili bağ alanlarındaki Thysanoptera türleri, mevsimsel yoğunlukları ve yayılış alanlarının belirlenmesi

Abstract: SummaryThis study investigated Thysanoptera species, their distribution, and seasonal abundance and relation to plant phenology in vineyard areas of Mardin province, in 2012Mardin province, in -2013. Surveys were conducted once in every three weeks in total of 22 vineyards of 8 districts of Mardin province between March and November according to plant phenology. Thrips were collected by beating plants in the field or by examining plant samples and the method of culturing in the laboratory. A total of 19 Thysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Özsemerci (2007) determined 31 thrips species in the seedless vineyards in Manisa Province and reported that R. vitis, H. globiceps, H. reuteri and Aeolothrips collaris were denser. Kaplan et al (2016) detected 19 thrips species in the vineyard areas of Mardin Province and he also found that H. globiceps species was more common.…”
Section: Thrips Speciesmentioning
confidence: 95%
See 1 more Smart Citation
“…Özsemerci (2007) determined 31 thrips species in the seedless vineyards in Manisa Province and reported that R. vitis, H. globiceps, H. reuteri and Aeolothrips collaris were denser. Kaplan et al (2016) detected 19 thrips species in the vineyard areas of Mardin Province and he also found that H. globiceps species was more common.…”
Section: Thrips Speciesmentioning
confidence: 95%
“…The thrips species and their economic importance have been reported by the previous studies conducted in the vineyard production areas in Türkiye (Kaplan et al, 2016;Kaplan & Bayhan, 2017, 2018. The Ministry of Agriculture technical staff report indicates that thrips are problem in vineyards of Mersin Province particularly in locations Mut and Tarsus.…”
Section: Introductionmentioning
confidence: 90%
“…Distribution in Türkiye: This species is found in Adana (Atakan and Tunç, 2004;Atakan, 2009;Sayan, 2010;Tunç et al, 2012), Afyon (Altınayar, 1981;Tunç et al , 2012), Ankara (Altınyar, 1981;Tunç and Strassen, 1984;Tunç et al, 2012); Antalya (Tunç, 1989;Tunç, 1990;Tunç, 1991;Tunç et al, 2012); Burdur (Tunç et al, 2012), Balıkesir (Çinkul, 2019), Isparta (Altınayar, 1981;Tunç et al, 2012), İzmir (Kılıç and Yoldaş, 2004;Tezcan et al, 2010;Şahin, 2012;Tunç et al, 2012;Güven, 2013), Konya (Altınayar, 1981;Tunç et al, 2012), Kütahya (Altınayar, 1981;Tunç et al, 2012), Manisa Tunç et al, 2012), Mardin (Kaplan et al, 2016), Mersin Tunç et al, 2012), Muğla (Tunç et al, 2012), Yozgat (Tunç et al, 2012).…”
Section: Aeolothripidaementioning
confidence: 99%
“…Thrips have a piercing-sucking mouth structure and they feed on different organs of the vines, causing silvery scar tissue, especially in vine fruits. In Türkiye, different Thysanoptera species, and their damage status and patterns in the vineyards production areas have been reported (Günaydın, 1972;İren, 1972;Cengiz, 1974;Maçan, 1984;Kaplan and Çınar, 1998;Altındişli et al, 2002;Doğanlar and Yiğit, 2002;Kaplan et al, 2016). Thrips species composition may vary from country to country, even in different geographical regions in the same country, and there may be differences in the economic importance of the species associated with vines.…”
Section: Introductionmentioning
confidence: 99%
“…The thrips species belonging to the genus Frankliniella, Scirtothrips and Thrips hawaiiensis (Morgan) are known to be the most economically damaging species (Mound and Teulon, 1995;Morse and Hoodle, 2006;Marullo and De Grazia, 2017). Thysanoptera fauna has been studied in various parts of Turkey including Antalya (Tunç, 1990;Tunç, 1991;Tunç, 1992), Manisa and Mardin province (Özsemerci et al, 2006;Kaplan et al, 2016). Moreover, in the Eastern Mediterranean Region, thrips species were studied in citrus (Nas et al, 2007;Ölçülü, 2014), vegetables (Atakan, 2007a;Atakan, 2010), fruits (Atakan, 2007b) and ornamentals (Atakan, 2011).…”
Section: Introductionmentioning
confidence: 99%